Tailoring polymer acceptors by electron linkers for achieving efficient and stable all-polymer solar cells. Issue 2 (16th August 2021) - Wu, Qiang; Wang, Wei; Wu, Yao; Sun, Rui; Guo, Jing; Shi, Mumin; Min, Jie
Abstract: The trade-off between efficiency and stability is a bit vague, and it can be tricky to precisely control the bulk morphology to simultaneously improve device efficiency and stability. Herein, three fused-ring conducted polymer acceptors containing furan, thiophene and selenophene as the electron linkers in their conjugated backbones, namely PY-O, PY-S and PY-Se, were designed and synthesized. The electron linker engineering affects the intermolecular interactions of relative polymer acceptors and their charge transport properties. Furthermore, excellent material compatibility was achieved when PY-Se was blended with polymer donor PBDB-T, resulting in nanoscale domains with favorable phase separation. The optimized PBDB-T : PY-Se blend not only exhibits maximum performance with a power conversion efficiency of 15.48%, which is much higher than those of PBDB-T : PY-O (9.80%) and PBDB-T : PY-S (14.16%) devices, but also shows better storage and operational stabilities, and mechanical robustness. This work demonstrates that precise modification of electron linkers can be a practical way to simultaneously actualize molecular crystallinity and phase miscibility for improving the performance of all-polymer solar cells, showing practical significance. Abstract : This paper demonstrates that electron linker engineering can be a practical strategy to fine-tune intermolecular interactions and molecular miscibility for simultaneously improving the efficiency and stability of all-polymer solar cells.